France : 2019 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for France. (IMF Staff Country Reports; Country Report, 2019)
This 2019 Article IV Consultation discusses that the French government revamped vocational training and professional development to foster labor market participation, especially for low-skilled workers, following key labor tax and labor code reforms enacted in its first year in office. In prioritizing the recommended reforms, the report highlights that the importance of carefully assessing the trade-offs and the proper sequencing of structural reforms and fiscal consolidation. The government's structural reform agenda is being put in place and growth is expected to gradually return to its potential level over the medium run. However, risks have risen, related to a disorderly Brexit, trade tensions, and a softening of activity in the euro area, but also to a slowdown in the domestic reform momentum. Building on the ongoing government reform agenda, policies should aim at addressing France's structural challenges-high public debt and spending, rising private sector indebtedness, high unemployment, inequality of opportunity, and sluggish productivity.